Conceptualising the context and contextualising the concept: corruption reconsidered - Arora Dolly (1993)
Placing corruption in the context of state-society relations, the author offers an analytical model for comprehending its realities. She conceptualises corruption in terms of relationship to (i) power and authority, (ii) law and policy, and (iii) the public space. Distinguishing between types of corruption viz., coercive, collusive and non-conjunctive, she indicates five major strategies which have been carefully utilised by its beneficiaries to promote and sustain the system of corruption in various contexts. Effort at eradicating corruption to be successful, she suggests, must address the task of diffusing the corruption sustaining contexts and strategies. Reproduced.
Keywords: Corruption